The Twitterization of News Making: Transparency and Journalistic Professionalism. (23rd August 2014) - Revers, Matthias
<x xml:space="preserve">Abstract</x> Twitter makes visible some of the most fundamental divides in professional journalism today. It reveals tensions about what constitutes news, the norms guiding journalists providing it, professional identity, and public service. This article argues that these tensions result from a clash between the institutional logic of professional control (Lewis, 2012)) and an ethic of transparency. Drawing from extensive research on a political press corps, involving observation, interviews, and analysis of tweets, this study witnesses the adoption of Twitter in the everyday working practices of reporters. It thereby also provides reasons why Twitter has been so successful in journalism. Tensions between professional control and transparency in journalism may, furthermore, be emblematic for divides in other professions today.